Genetic diversity of imported PRRSV-2 strains, 2005–2020, Hungary - Jakab, Szilvia; Kaszab, Eszter; Marton, Szilvia; Bányai, Krisztián; Bálint, Ádám; Nemes, Imre; Szabó, István (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome virus 2 (PRRSV-2) remains sporadic in Europe. In this study, we investigated the molecular epidemiology of PRRSV-2 infections encompassing 15 years in Hungary. Partial (423 bp long) ORF5 sequences (n = 44) from 20 Hungarian pig herds were analysed. The study strains fell into two genetic lineages, L1 and L5, being L5 strains more prevalent (88.6 vs 11.4%). Pairwise sequence identities within Hungarian representative PRRSV-2 strains ranged between 84.7 to 100% (nucleotide, nt) and 85 to 100% (amino acid, aa). When compared with reference strains, identity values fell between 87% and 100% (L1, nt 87-91%, aa 87-93%, reference strain IAF-exp91; L5, nt 87-100%, aa 88-100%, reference strain Ingelvac MLV). Epidemiologic examination implied that the majority of L5 strains were imported repeatedly from other European countries where Ingelvac MLV was approved for routine use. The emergence of L1 strains was thought to be associated with a single introduction and subsequent dissemination between pig farms of a large integrator. Results presented here contribute to a better understanding of the epizootiology of PRRSV-2 infections and shed light on the genetic diversity of viral strains in non-endemic countries.